Response to "Rudat Sasambo (RUSA) Diabetes Mellitus Exercise According to FITT, Reduce Blood Glucose Levels in Patients with Type 2 Diabetes Mellitus" - Bahtiar Bahtiar; David Ackah; Pius Weraman (Aloha International Journal of Health Advancement (AIJHA), 2025)
Letter to editor: abstract is not required